The Role Of Parental Involvement In Enhancing Students’ Motivation To Learn English - Ribka Natalia Br. Hutabarat; Virginia Gabrella Sengkey (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study was designed to determine whether there is a significant correlation between parental involvement and students' motivation to learn English among 10th-grade students at one of the high schools in North Sulawesi. In addition to that, the researchers also wanted to find out the levels of parental involvement and students’ motivation in learning English. The questionnaires that were used in this research were adapted from Alam and Rosli (2016) and Gardner (2011). This study involved 70 respondents from grade 10 IPA 1, 10 IPA 3, 10 IPA 4 and 10 IPS 1 at a private high school in North Sulawesi. The findings showed that the level of parental involvement was 3.25, which indicates a moderate parental involvement. Furthermore, the findings showed that the level of students’ motivation in learning English was 4.12, which is interpreted as high motivation. Moreover, the results indicated a significant positive correlation between parental involvement and students’ motivation to learn English, as the p-value was .000. Thus, parental involvement is a significant factor that can help increase students’ motivation to learn English.